Properties of Different Varieties of Durian - Supeeraya Arsa; Angkana Wipatanawin; Rachit Suwapanich; Orachorn Makkerdchoo; Niphattha Chatsuwan; Pensiri Kaewthong; Praphan Pinsirodom; Ruchira Taprap; Ratiporn Haruenkit; Sumitra Poovarodom; Martyna Lubinska-Szczyge_; Elena Katrich; et al. (My University, 2021)
Durian (Durio zibethinus Murr.), like many other exotic, tropical, and conventional fruits, is important in the prevention of different diseases. In this study, the characterization of the main bioactive compounds of the most popular cultivars of durian and their properties are described. The changes in the quality indices of the antioxidant status were determined by CUPRAC, ABTS, FRAP, DPPH, and ORAC assays. The profiling of phytochemicals was carried out by Fourier transform infrared (FTIR) spectroscopy and differential scanning calorimetry (DSC). For the first time, in vitro studies were performed by the interaction of extracted durian polyphenols with human serum proteins (HSP) such as human serum albumin (HSAlb), fibrinogen (HSFib) and globulin (HSGlo) as novel biomarkers of coronary artery disease (CAD). The fluorescence measurements of the resulting intensity and calculated binding properties of the interaction of polyphenols with proteins showed that the most reactive was Monthong durian cultivar. This study suggests that durian cultivars have relatively strong antioxidant, binding, and health potentials and could be a significant source of natural antioxidants used in daily fresh consumption and for functional foods.
Keywords: ABTS; Phytochemicals and Antioxidant Activities